Program Penerapan Mitigasi Bencana Gempa Bumi Di Ponpes Nurul Wathan Lombok Tengah NTB Berorientasi Pada Penurunan Magnet Bumi Akibat Pergerakan Sesar Patahan - Made Sutha Yadnya; Dwi Ratnasari; Abdulah Zainuddin; Bulkis Kanata; Teti Zubaidah; Paniran Paniran (Jurnal Gema Ngabdi, 2020)
The program that was implemented at Nurul Wathan (NW) was the result of research at the Rembitan Observatory to measure the earth's magnetism using a device called Proton. The international unit for measuring the earth's magnetism is the Tesla, specifically the nTesla earth magnet (Nano Tesla). The stages of implementing the solution are adjusted to the characteristics of the stages of the disaster cycle. During a disaster, full of activities in an emergency situation, post-disaster, reduce the complexity of the problems in reconstruction and rehabilitation. Pre-disaster requires thorough planning. Communities that are exposed to disasters are very diverse. For those who have been educated or those who have not received formal education, they need to understand the importance of disaster risk reduction (DRR).